Financial and legal regulation of relations in the field of provision of international grants to budgetary institutions - Чемерис, М. С. (Київський національний університет імені Тараса Шевченка, 2025)
The article reveals the results of the analysis of the financial and legal regulation of relations in the field of providing international grants to state authorities, local governments and other budgetary institutions involved in the implementation of the project (program) of international technical assistance. The relevance and degree of research of the specified topic are indicated. It is noted that in the context of international financial law, grants are a special form of assistance in cross-border financial relations, characterized by irrevocability and targeted allocation of funds. The state of budgetary and legal consolidation of international grants as revenues of the state and local budgets is highlighted. The features of an international grant as a legal category are indicated. The features of treasury servicing of budget funds that come as grants within the framework of assistance programs and grants of the European Union, governments of foreign states, international organizations, donor institutions and as credits (loans) attracted by the state from foreign states, foreign financial institutions and international financial organizations are highlighted. It is noted that the shortcoming of budgetary and legal regulation is the absence in the Budget Code of Ukraine of provisions regulating the relations that arise between the grantor, beneficiary, recipient and executor (who implements the grant project (program) or part thereof), does not contain requirements for an international agreement on the basis of which obligations arise, including monetary ones, for the grantor and the state (territorial community) as a beneficiary in the event of receiving a grant. It is noted that a shortcoming of budgetary and legal regulation is the absence in the Budget Code of Ukraine of provisions regulating the relations that arise between the grantor, beneficiary and recipient (who implements the grant project (program) or part thereof), does not contain requirements for an international treaty on the basis of which obligations arise, including monetary ones, for the grantor and the state (territorial community) as a beneficiary in the event of receiving a grant. It is noted that the special regulatory legal acts of Ukraine that regulate relations in the field of attracting international technical assistance, in particular in the form of grants, are the Resolution of the Cabinet of Ministers of Ukraine dated 15.02.2002 No. 153, which approved the Procedure for attracting, using and monitoring international technical assistance, and the Resolution of the Cabinet of Ministers of Ukraine dated 11.10.2024 No. 1163 “On approving the Procedure for maintaining the Register of projects (programs) of international technical assistance”, the main international agreements that contain standards for providing international grants are highlighted. The concept of international technical assistance, grants as a separate form of it is disclosed. The requirements of the legislation on the registration of grant projects as projects (programs) of international technical assistance, the features of the subject composition of these relations, as a special subject of financial and legal regulation are highlighted. A list of state authorities that, on the basis of the provisions of special laws that regulate their activities, may receive grants within the framework of international technical assistance is provided. Proposals were made to adopt the Law of Ukraine “On International Assistance, and to make amendments to Articles 2, 43 and 48 of the Budget Code of Ukraine in terms of regulating the specifics of relations with the attraction of grants by budgetary institutions within the framework of international technical assistance, making budgetary commitments and carrying out operations with these funds.

В статті розкрито результати аналізу фінансово-правового регулювання відносин в сфері надання міжнародних грантів органам державної влади, органам місцевого самоврядування та іншим бюджетним установам, які залучаються в рамках реалізації проекту (програми) міжнародної технічної допомоги. Вказано актуальність та ступінь дослідженості вказаної теми. Зазначено, що у контексті міжнародного фінансового права гранти є особливою формою допомоги в транскордонних фінансових відносинах, що характеризується безповоротністю та цільовим призначенням коштів. Висвітлено стан бюджетно-правового закріплення міжнародних грантів як надходжень державного та місцевих бюджетів. Вказано риси міжнародного гранту як правової категорії. Висвітлено особливості казначейського обслуговування коштів бюджет, які надходять як гранти в рамках програм допомоги і грантів Європейського Союзу, урядів іноземних держав, міжнародних організацій, донорських установ та як кредити (позики), залучені державою від іноземних держав, іноземних фінансових установ і міжнародних фінансових організацій. Зазначено, що недоліком бюджетно-правового регулювання є відсутність на сьогодні в Бюджетному кодексі України положень, що регулюють відносини, що виникають між грантодавцем, бенефіціаром, реципієнтом та виконавцем (який реалізує грантовий проект (програму) або його частину), не містить вимоги до міжнародного договору, на підставі якого виникають зобов’язання, в тому числі грошові, у грантодавця та держави (територіальної громади) як бенефіціара в разі одержання гранту. Зазначено, що спеціальними нормативно-правовими актами України, що регулюють відносини в сфері залучення міжнародної технічної допомоги, зокрема у формі грантів, є Постанова Кабінету Міністрів України від 15.02.2002 № 153, якою затверджено Порядок залучення, використання та моніторингу міжнародної технічної допомоги, та Постанова Кабінету Міністрів України від 11.10.2024 року № 1163 “Про затвердження Порядку ведення Реєстру проектів (програм) міжнародної технічної допомоги”, висвітлено основні міжнародні договори, які містять стандарти надання міжнародних грантів. Розкрито поняття міжнародної технічної допомоги, грантів як окремої її форми. Висвітлено вимоги законодавства щодо реєстрації грантових проектів як проектів (програм) міжнародної технічної допомоги, особливості суб’єктного складу цих відносин, як спеціального предмету фінансово-правового регулювання. Наведено перелік органів державної влади, які на підставі положень спеціальних законів, які регулюють їх діяльність можуть отримувати гранти в рамках міжнародної технічної допомоги. Висловлено пропозиції щодо прийняття закону України “Про міжнародну допомогу, та внесення доповнень до статей 2, 43 та 48 Бюджетного кодексу України в частині врегулювання особливостей відносин із залучення бюджетними установами грантів в рамках міжнародної технічної допомоги,  взяття бюджетних зобов’язань і здійснення операцій з цими коштами.
Фінансово-правове регулювання відносин в сфері надання міжнародних грантів бюджетним установам
Keywords: grant; international grant; international technical assistance; budget revenues; budgetary institutions; own revenues.; грант; міжнародний грант; міжнародна технічна допомога; надходження бюджету; бюджетні установи; власні надходження.